Essential oils composition of Polystichum montevidense (Spreng.) Rosenst (Dryopteridaceae) and Podocarpus parlatorei Pilg. (Podocarpaceae) - Labuckas, Diana Ondina (2005)
The essential oils of Polystichum montevidense (Spreng.) Rosenst. (Dryopteridaceae) and Podocarpus parlatorei Pilg. (Podocarpaceae) were analyzed for the first time by means of GC and GC-MS. From Polystichum montevidense sixteen compounds were identified, representing 98.0% of the oil, whereas Podocarpus parlatorei seventeen compounds were identified, representing 97.7% of the oil. Polystichum montevidense contained higher amounts of α-pinene (21.3%), α-terpineol (14.8%), pulegone (14.7%), and α-muurolene (10.2%), whereas the major oil constituents of Podocarpus parlatorei were found to be terpinen-4-ol (29.0%), germacrene D (17.7%) and α-eudesmol (16.5%).